Malonylation/Decarbalkoxylation of Furan Derivatives as Key Steps for the Preparation of Nonactic Acid Derivatives. Part II [1] - Simone, Jean-Mary; Loiseau, François; Carcache, David; Bobal, Pavel; Jeanneret-Gris, Julie; Neier, Reinhard (My University, 2007)
A malonylation/decarbalkoxylation sequence from 2-substituted furans was investigated in view of developing a scalable synthesis of hydrophobic nonactic acid analogues.
Keywords: Heterocycles; Decarbalkoxylation; Nonactic acid; Natural-like